2006
DOI: 10.1108/02640470610714233
|View full text |Cite
|
Sign up to set email alerts
|

How the presentation of electronic gateway pages affects research behavior

Abstract: Purpose -The paper aims to provide details of a study conducted at Hunter College Libraries in fall 2005, the focus of which was how presentation of initial digital resource pages (or gateway pages) on the library's web site impacted students' subsequent steps in the research process. Design/methodology/approach -A group of 16 students from English and History classes at Hunter College were recruited to participate after having had basic library instruction. They were given computer-based key tasks to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Existing body of literature presents a number of studies confirming certain attributes of e‐learning system result in higher learning motivation or better learning behaviors, such as reading, searching, browsing, or collaborating (Jung et al , 2008; Given et al , 2007; Finder et al , 2006; Li and Rubin, 2004; Tong, 2009). Thus, it can be argued that e‐learning system quality plays a critical factor in learning behaviors and learners' achievements.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Existing body of literature presents a number of studies confirming certain attributes of e‐learning system result in higher learning motivation or better learning behaviors, such as reading, searching, browsing, or collaborating (Jung et al , 2008; Given et al , 2007; Finder et al , 2006; Li and Rubin, 2004; Tong, 2009). Thus, it can be argued that e‐learning system quality plays a critical factor in learning behaviors and learners' achievements.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Based on previous use with other sites, he expected to see more information pop up (link title) that would explain where the link will go. As found in a recent study on how presentation of digital resource pages affect human behavior (Finder et al , 2006), confusing terminology and icons can lead to errors or even failure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that students in general experience difficulties with the search process in databases (Finder et al, 2006;Mittermeyer, 2005, Valentine 2001). This study focused solely on students with print disabilities and therefore lacks a control group of non-print disabled students against which the results of students with print disabilities could be measured.…”
Section: Limitationsmentioning
confidence: 99%